2022
DOI: 10.1136/bmjopen-2021-058016
|View full text |Cite
|
Sign up to set email alerts
|

Development of an intervention to improve informational continuity of care in older patients with polypharmacy at the interface between general practice and hospital care: protocol for a participatory qualitative study in Germany

Abstract: IntroductionOlder patients with multimorbidity, polypharmacy and related complex care needs represent a growing proportion of the population and a challenge for healthcare systems. Particularly in transitional care (hospital admission and hospital discharge), medical errors, inappropriate treatment, patient concerns and lack of confidence in healthcare are major problems that may arise from a lack of information continuity. The aim of this study is to develop an intervention to improve informational continuity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…23 Continuity of care is a key indicator of a strong primary care system, which has shown to bring benefits to population health. 67,68 Our study showed that continuity of care is the most important appointment attribute for German primary care patients. It has been widely discussed in the existing literature that the respondents usually attached high importance to the continuity of care.…”
Section: Results Interpretation and Comparison To The Existing Litera...mentioning
confidence: 79%
“…23 Continuity of care is a key indicator of a strong primary care system, which has shown to bring benefits to population health. 67,68 Our study showed that continuity of care is the most important appointment attribute for German primary care patients. It has been widely discussed in the existing literature that the respondents usually attached high importance to the continuity of care.…”
Section: Results Interpretation and Comparison To The Existing Litera...mentioning
confidence: 79%
“…However, in this respect they mainly consider cooperation between physicians and pharmacists [ 19 ], whereas stakeholders in our study stressed the importance of involving healthcare assistants as well. In Germany, healthcare assistants play an important role in primary care, and are often trained to take on additional tasks and to share responsibilities with the GP [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants provided written informed consent before participating in the study. The rationale of sub-study 1 was previously published in a study protocol [39]. Sub-study 1 is divided into two parts.…”
Section: Hyperion-transcare Projectmentioning
confidence: 99%
“…The first part reported here is aimed at exploring, understanding and describing the care setting and stakeholder-specific perspectives, experiences and needs regarding continuity of medication management during care transitions, using qualitative expert interviews. In the second part, the qualitative expert interview results were further analyzed in co-design workshops along with representatives of these different stakeholder groups to come up with a new intervention to improve continuity of medication management in transitions of care [39,40]. The recruitment of stakeholders and the results of the workshops are published elsewhere [40].…”
Section: Hyperion-transcare Projectmentioning
confidence: 99%
See 1 more Smart Citation